Cluster crossover trial of head positioning in acute stroke - Anderson, C; Arima, H; Lavados, P; Billot, L; Hackett, M; Olavarría, V; Venturelli, P; Brunser, A; Peng, B; Cui, L; Song, L; Rogers, K; et al. (Massachusetts Medical Society, 2017)
Background Outcomes in patients with acute ischemic stroke could be improved by lying flat, i.e., fully supine with the back horizontal and the face upwards, to increase cerebral perfusion. Evidence to guide head positioning after stroke is limited and the lying flat position may increase the risk of pneumonia. Methods In a pragmatic, cluster randomized crossover trial conducted in nine countries, we randomly assigned 11,094 patients with acute stroke, 85% of which were ischemic, to receive care lying-flat or sitting-up (≥30 degrees) commencing soon after hospital admission and continued for 24 hours. The primary outcome was disability at 90 days on the modified Rankin scale (range 0 to 6 with higher scores indicating greater disability and a score of 6, indicating death). Results The median interval between the onset of stroke symptoms and assuming the assigned body position was 14 hours (interquartile range, 5 to 35 hours). Patients in the lying-flat group were less likely to maintain the position over 24 hours than in the sitting-up group (87% vs. 95%; respectively; P<0.0001). In a proportional odds model, there was no significant shift in the distribution of 90-day disability outcomes on the global modified Rankin scale between patients in the lying-flat and sitting-up groups (odds ratio 1.01; 95% confidence interval, 0.92 to 1.10; P=0.84). Mortality was 7.3% in the lying-flat group and 7.4% in the sitting-up group (P=0.83). There was no significant difference between the groups in serious adverse events including pneumonia. Conclusions Disability outcomes after acute stroke were no different between lying flat and elevating the head 30 degrees for 24 hours.